A socio-cultural model of Judean ethnicity: A proposal - Cromhout, Markus (HTS teologiese studies, 2006)
This article focuses on the matter of Judean (“Jewish”) ethnic identity during the first century CE. New Testament scholarship lacks an overall interpretive framework by which Judean identity can be understood. Appreciation of what informed the entire process of Judean ethnic identity formation in the first century, or at any period for that matter, is lacking. This lack of interpretive framework is rather acute in scholarship on the historical Jesus, where the issue of Judeanness (“Jewishness”) is most strongly debated. A Socio-Cultural Model of Judean Ethnicity is developed, as being a synthesis of (1) Sanders’ notion of covenantal nomism, but reappropriated to serve as an ethnic descriptor, (2) Berger and Luckmann’s theories on the sociology of knowledge, (3) Dunn’s “four pillars of Second Temple ‘Judaism’” and his “new perspec-tive” on Paul, (4) cultural anthropology in the form of modern ethnicity theory, and lastly, (5) Duling’s Socio-Cultural Model of Ethnicity. The proposed model is termed covenantal nomism. It is a pictorial representation of the Judean “symbolic universe” which, as an ethnic identity, is proposed to be essentially primordialist.